A randomised multicentre study of human milk versus formula and later development in preterm infants. Issue 2 (March 1994) - Lucas, A; Morley, R; Cole, T J; Gore, S M
Abstract : Whether breast milk influences later neurodevelopment has been explored in non-randomised studies, potentially confounded by social and demographic differences between feed groups. Here in a strictly randomised prospective multicentre trial, Bayley psychomotor and mental development indices (PDI and MDI) were assessed at 18 months postterm in survivors of 502 preterm infants assigned to receive, during their early weeks, mature donor breast milk or a preterm formula. These diets were compared as sole enteral feeds or as supplements to the mother's expressed breast milk. No differences in outcome at 18 months were seen between the two diet groups despite the low nutrient content of donor milk in relation to the preterm formula and to the estimated needs of preterm infants. These results contrast with those reported from our parallel two centre study that compared infants randomly assigned a standard term formula or the preterm formula during their early weeks; those fed standard formula, now regarded as nutritionally insufficient for preterm infants, were substantially disadvantaged in PDI and MDI at 18 months post-term. It is shown here that infants from that study fed solely on standard formula had significantly lower developmental scores at 18 months than those fed on donor breast milk in the present study; yet the standard formula had a higher nutrient content than the donor milk. Thus, donor milk feeding was associated with advantages for later development that may have offset any potentially deleterious effects of its low nutrient content for preterm infants. As these outcome advantages were not confounded by the social and educational biases usually associated with mothers' choice to breast feed, our data add significant support to the view that breast milk promotes neurodevelopment.